Regulating autonomous vehicles: Liability paradigms and value choices - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2021)
In technological terms, this decade hardly resembles the last: mass and private communications are now dominated by a small group of online social media platforms; spending currency is becoming entirely electronic and digital; unmanned and stabilised aerial imaging has become affordable and accessible, to name but a few prominent examples. A significant contributing factor to this change has been the unprecedented developments in creating systems that can function with minimal human intervention and process new datasets quickly to improve its decision-making abilities, although at the same time, concerns have been raised as to whether these technical complexities may obscure accountability when mistakes or malfunctions occur. The next decade may well see the widespread implementation of another application of such systems: self-driving vehicles or automated vehicles (AVs), which are supposed to help societies achieve greater transportation efficiencies, road safety for road users and overall economic productivity. On a theoretical level, it may seem that AVs do not represent a very big step forward from where we are, considering that some of their core technologies are already being used by human-operated cars today, such as sensors, GPS and image capture. There is also already some degree of automation technology that has been around for some time in certain cars, for instance, in the form of cruise 148control and self-parking. However, in practical, legal terms, one can imagine how the eventual complete removal of a human driver in the equation changes everything for regulators, manufacturers and road users. This is especially so in the context of road traffic accidents that result in significant damage to property or persons – perhaps the most visceral fear of the public when it comes to mainstream acceptance of AVs being used for daily travel, which is now considered an inevitability.